GABA-A and GABA-B Receptors in Filial Imprinting Linked With Opening and Closing of the Sensitive Period in Domestic Chicks (Gallus gallus domesticus) - Aoki, Naoya; Yamaguchi, Shinji; Fujita, Toshiyuki; Mori, Chihiro; Fujita, Eiko; Matsushima, Toshiya; Homma, Koichi J. (Frontiers in Physiology, 2018)
Filial imprinting of domestic chicks has a well-defined sensitive (critical) period lasting in the laboratory from hatching to day 3. It is a typical model to investigate the molecular mechanisms underlying memory formation in early learning. We recently found that thyroid hormone 3,5,3ʹ-triiodothyronine (T3) is a determinant of the sensitive period. Rapid increases in cerebral T3 levels are induced by imprinting training, rendering chicks imprintable. Furthermore, the administration of exogenous T3 makes chicks imprintable on day 4 or 6 even after the sensitive period has ended. However, how T3 affects neural transmission to enable imprinting remains mostly unknown. In this study, we demonstrate opposing roles for gamma-aminobutyric acid (GABA)-A and GABA-B receptors in imprinting downstream of T3. Quantitative reverse transcription polymerase chain reaction and immunoblotting showed that the GABA-A receptor expression increases gradually from day 1 to day 5, whereas the GABA-B receptor expression gradually decreases. We examined whether neurons in the intermediate medial mesopallium (IMM), the brain region responsible for imprinting, express both types of GABA receptors. Immunostaining showed that morphologically identified putative projection neurons express both GABA-A and GABA-B receptors, suggesting that those GABA receptors interact with each other in these cells to modulate the IMM outputs. The roles of GABA-A and GABA-B receptors were investigated using various agonists and antagonists. Our results show that GABA-B receptor antagonists suppressed imprinting on day 1, while its agonists made day 4 chicks imprintable without administration of exogenous T3. By contrast, GABA-A receptor agonists suppressed imprinting on day 1, while its antagonists induced imprintability on day 4 without exogenous T3. Furthermore, both GABA-A receptor agonists and GABA-B receptor antagonists suppressed T3-induced imprintability on day 4 after the sensitive period has ended. Our data from these pharmacological experiments indicate that GABA-B receptors facilitate imprinting downstream of T3 by initiating the sensitive period, while the GABA-A receptor contributes to the termination of the sensitive period. In conclusion, we propose that opposing roles of GABA-A and GABA-B receptors in the brain during development determine the induction and termination of the sensitive period.